The strategic planning approach on knowledge accumulation in the internationalization process: A proposed model - Nik Muhammad, Nik Maheran; Muhammad, Zainuri; Ismail, Mohammad (2008)
Knowledge has been considered as a critical role in generating organizational advantage and uphold by organizational researchers as the key resource to create sustainable competitive advantages.The behavioral models dealing with the internationalization process are Uppsala internationalization Process Model (U-Model),Innovation Internationalization Process Model (I-Model)and Knowledge-based view theory. This study proposed to integrate insights from the KBV theory, internationalization process model and Forsgren’s critical review of the concept of learning in the Uppsala internationalization process model to develop a new framework for knowledge management in exporting firms.The objective of the study thus is to propose the role of experiential knowledge, knowledge from imitative learning, in corporat ion with other unit, staffing, networking and informational knowledge in the internationalization process.